2018
DOI: 10.1111/nmo.13461
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy of patients with irritable bowel syndrome: A systematic review of randomized controlled trials

Abstract: Our findings suggest that exercise is potentially a feasible and effective treatment for IBS patients. However, because of methodologic issues, no firm conclusions could be drawn about the true effects of this intervention. Researchers should design a rigorous study to assess the effects of exercise on IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 40 publications
(178 reference statements)
3
52
0
4
Order By: Relevance
“…These heterogeneous conditions are also described as “disorders of gut-brain interaction,” as they can be classified as disorders that span both the GI and the neurological systems ( Figure 1 ). People with these FGIDs have high rates of psychological comorbidity (Wu, 2012 ) and treatments aimed at stress and anxiety [e.g., hypnotherapy (Simon et al, 2019 ), cognitive behavioral therapy (Everitt et al, 2019 ), exercise (Zhou et al, 2019 ), and antidepressants Kulak-Bejda et al, 2017 ] can be effective treatments.…”
Section: Irritable Bowel Syndrome and Functional Gastrointestinal Dismentioning
confidence: 99%
“…These heterogeneous conditions are also described as “disorders of gut-brain interaction,” as they can be classified as disorders that span both the GI and the neurological systems ( Figure 1 ). People with these FGIDs have high rates of psychological comorbidity (Wu, 2012 ) and treatments aimed at stress and anxiety [e.g., hypnotherapy (Simon et al, 2019 ), cognitive behavioral therapy (Everitt et al, 2019 ), exercise (Zhou et al, 2019 ), and antidepressants Kulak-Bejda et al, 2017 ] can be effective treatments.…”
Section: Irritable Bowel Syndrome and Functional Gastrointestinal Dismentioning
confidence: 99%
“…Other Chinese studies have reported improvement in IBS with Tai chi and Baduanjin activity (reported in Zhou et al 65 ).…”
Section: Exercise Associated With Specific Skills or Knowledgementioning
confidence: 91%
“…Several clinical trials show a benefit of physical exercise in IBS patients, as suggested by a recent systematic review 65 . From a practical point of view, physical exercise may be classified as those easily self-directed (i.e., walking, running, swimming…) and those which require specific knowledge, skills, or mentoring (like yoga).…”
Section: Direct Evidence Of the Benefits Of Physical Activity In Ibsmentioning
confidence: 91%
“…These positive effects persisted in 39 patients followed up for a median of 5.2 years. 48 A systematic review from 2018 summarised findings from 14 RCTs of exercise therapy in IBS, involving a total of 683 patients, 49 and included the two aforementioned RCTs. 46,47 Other interventions studied were diverse, including aerobic exercise, yoga, Tai Ji, and mountaineering.…”
Section: Exercisementioning
confidence: 99%